Crack healing in SUS304 stainless steel by electropulsing treatment. (1st February 2016) - Yu, Tao; Deng, Dewei; Wang, Gang; Zhang, Hongchao
Abstract: The research about repair of metal cracks plays an important role in promoting the development of remanufacturing engineering. Crack in the SUS304 stainless steel was treated by electropulsing with peak current density of 4.1 kA/mm 2 . After seven times of electropulsing treatment, continuous healing areas in both left and right side of crack were formed. The process of rapid melting and solidification occurred in healing areas, columnar crystals and fine recrystallization zone were formed at the same time. The detour and joule heating effects were the main reason to realize crack healing and detailed healing processes were discussed. Highlights: Overlapping oval healing areas formed after electropulsing treatment. The process of rapid melting and solidification were occurred at the healing areas. The healing areas were composed of columnar crystals. Detour and Joule heating effects were the main reasons of crack healing. Healing effect brought by each pulse discharge showed the tendency of gradually weakened.